THE VERB “HIT” IN PALEMBANG LANGUAGE: NATURAL SEMANTIC METALANGUAGE STUDY - Jeni Arasyita Tazami; Agus Subiyanto (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Verb is one of the major lexical classes in language. There are three types of verbs, one of which is action verb, as found in the verb ‘hit’. The verb "hit" is a verb which has two meanings namely DO and HAPPEN forming the universal syntactic meaning:  'X does something to Y because that something happens to Y '. This paper aims to get a clear description of the verb “hit” categorization in Palembang language using Natural Semantic Metalanguage (NSM) theory. This research uses a qualitative approach to understand the forms of the verb "hit" in Palembang language and their explications within the NSM theory. The data used in this study are taken from native speakers of Palembang language. The results show that the categorization of the verb "hit" in Palembang language can be classified based on the body parts (hand, fingers) or the tools used to hit and based on the objects hit (head, face, or any body’s part).